INTERNALISASI NILAI-NILAI PENDIDIKAN KARAKTER RELIGIUS PADA ANAK USIA DINI DI RA PERSIS 39 JAMANIS KABUPATEN TASIKMALAYA - Ai Siti Mutmainah (Tumbuh Kembang: Kajian Teori dan Pembelajaran PAUD, 2020)
The purpose of this study is to know 1) the values of religious character education developed, 2) the process of internalizing the values of religious character education, and 3) the supporting and inhibiting factors of the process of internalizing the values of religious character education in RA Persis 39 Jamanis Tasikmalaya Regency . This research uses descriptive analytic method with a qualitative approach. The data collection techniques are carried out through interviews, observations, and documentation The research subjects are the Principal, Teachers, and students. Data analysis is done by selecting and sorting the answers of the data obtained then collected for analysis and conclusions drawn. This study found that 1) The values of religious characters developed were divine values and insyaniyah 2) The process of internalizing religious character education values was first, the stage of giving knowledge and understanding both inside the classroom and outside, Second, the habituation stage. Third, the stage of trans-internalization, and 3) Supporting and inhibiting factors of the internalization process of religious character education values, namely factors that support and inhibit the role and policies of the principal, the cooperation of the school and parents. As for the inhibiting factor, the environment outside the school is so rapid with the presence of sophisticated technology and does not get a good example from parents in his home